Pengaruh Pemahaman Masyarakat terhadap Pergantian Nasab Anak oleh Ayah Angkat Perspektif Hukum Islam (Studi Kasus Desa Jabung Lampung Timur) - Mu'in, Fathul; Yanti, Meli (Syakhsiyah Jurnal Hukum Keluarga Islam, 2023)
An adopted child often has his lineage transferred to his adoptive father. A child's nasab (lineage) in Islam is very important, nasab is the goal of Islamic law,especially Hifzu Nasab, so it must be protected by the family. An adopted child's lineage is only passed on to his biological father, even if the child is adopted from childhood, he still cannot transfer his lineage from his biological father to his adoptive father, however, the prohibition on transferring his lineage to his adoptive father is also explained in Islamic law. A child's lineage that is not suitable will bring disaster to that child, as happened in Jabung Village, East Lampung. The type of research carried out by researchers is field research using qualitative methods. Meanwhile, the data collection techniques used include observation, interviews and notes. Regarding the analysis technique used, namely using inductive thinking, inductive is a way of thinking that arises from specific data and empirical facts in the field which are synthesized, processed, studied, then the meaning is drawn in the form of general conclusions. This research uses an approach with Islamic legal theory, especially those related to lineage and adoption. From this research, it can be concluded that in the community's understanding of changes in children's lineages carried out by adoptive fathers in Jabung village, East Lampung, some people make their foster children their bloodlines. Factors that influence social ignorance are education and tradition. Islamic law prohibits adoption by affixing the adoptive father's name to the adopted child.